Legal plunder: the predatory dimensions of criminal justice - Page, Joshua (Chicago studies in American politics, 2025)
"Alongside the rise of mass incarceration, a second profound development has transpired. Since the 1980s, US policing and punishment have been remade into tools for stripping resources from the nation's most oppressed communities and turning them into public and private revenues. Legal Plunder explores this development's origins, operations, consequences, and the political struggles that surround it. Leveraging historical and contemporary evidence and original ethnographic research, Joshua Page and Joe Soss analyze what they call the predatory dimensions of criminal legal governance. Readers will learn how, as tax burdens have declined for the affluent, practices that criminalize, police, and punish have been retrofitted to siphon resources from subordinated groups, subsidize governments, and generate corporate profits. Financial extraction, now a core function of the country's sprawling criminal legal apparatus, compounds race, class, and gender inequalities and injustices. We can no longer afford to overlook legal plunder or the efforts to dismantle it"--